P, dit X / P, X says dans le genre journalistique : entre effacement et brouillage des niveaux d’énoncé - Raluca NITA (E-REA)
This article deals with the identification of reported speech in journalistic texts when it takes the form of P, dit X / P, X says. It raises the question of the boundaries between narrative and reported clause due to a cluster of elements: the reported clause appears in final or median position while linguistic and punctuation markers within P do not allow to identify P as a reported clause; at the same time, the content of P is involved in the narrative of journalistic text. The status of P is dependent on the journalistic genre in French and English and in most of the cases both the primary speaker and the reported speaker commit to the truth value of P. This reported speech is ambiguous and oscillates between the current speech situation and the reported speech situation on account of the place it can occupy in the text structure, of the type of article (general information, specific events, portrait of a public person) and of the reported speech structure and linguistic internal markers.